2021
DOI: 10.11648/j.ijcu.20210501.20
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Bone Metastases and PSA Among Prostate Cancer Patients at Kilimanjaro Christian Medical Centre from June 2018 to May 2019

Abstract: Prostate cancer is a leading cause of cancer death in men, second only to lung cancer. Bone metastasis is a common complication in prostate cancer patients that can cause bone pain and pathological fracture. PSA, Gleasons score, clinical T stage have been developed to integrate multiple clinical metastatic disease in prostate cancer patients. Bone radiography is used to rule out bone metastasis. It's common to have bone metastasis when PSA level is high and histology of poorly differentiated adenocarcinoma. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(16) They are consistent with other studies which also showed that increasing age is associated with more skeletal metastasis. (5,7)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(16) They are consistent with other studies which also showed that increasing age is associated with more skeletal metastasis. (5,7)…”
Section: Discussionmentioning
confidence: 99%
“…In our setting more than half of patients with prostate and Breast cancer have been shown to present with bone metastasis metastasis. (7)(5) These cancers have also been shown to be the commonest primary cancers in studies done in other parts of the world. (1,2,9,19,20)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations